COMMUNITY SERVICE "RECHARGE YOUR ENERGY": UNPACK THE SECRET OF ANEMIA-FREE PRODUCTIVE LIFE WITH THE IMPLEMENTATION OF MUNG BEAN JUICE IN STUDENTS GRADE 12 SMAN 1 BATUJAJAR, BATUJAJAR DISTRICT, WEST BANDUNG REGENCY - Deasy, Afrieani; Megasari, Mona; Atira, Atira; Supiyanto, Supiyanto; Irwani Pr, Nabila; Azharil, Firda; Ayu, Diah (Jurnal Pengabdian Masyarakat Sabangka, 2025)
Adolescence is a crucial developmental stage characterized by rapid physical and mental changes that require proper nutrition and sufficient energy intake. At SMAN 1 Batujajar, a significant number of students show signs of anemia, indicating the need for targeted health education. This study evaluates the effectiveness of an anemia-prevention seminar titled “Recharge Your Energy: Unlocking the Secrets to a Productive, Anemia-Free Life” in enhancing students’ knowledge about the causes, symptoms, and prevention of anemia, including the benefits of consuming mung bean juice. Using a quantitative descriptive design, 91 participants completed pre-tests and post-tests, along with health checks such as blood pressure and conjunctiva examinations. Findings revealed that 62 students were clinically identified as anemic. Knowledge levels improved after the seminar, demonstrating increased understanding of iron intake, balanced nutrition, healthy lifestyle habits, and mung bean juice benefits. The program proved effective and is recommended for ongoing school-based health promotion.